Observation on the foundation of kinetic theory of gases - U. Basu; M. Dutta (International Journal of Mathematics and Mathematical Sciences)
This paper deals with the study of the mathematical foundation of the Kinetic theory of gases. The significance of the Boltzmann model for a system of particles treated by classical mechanics is briefly explained. An apparent, but inherent difficulty in this model is pointed out.